Early Detection of Diseases And Abnormalities In The Respiratory System Using Certainty Factor Method - Mohammad Arman Prambudi; Achmad Muchayan (IJEEIT : International Journal of Electrical Engineering and Information Technology, 2021)
Health is a very important factor in the human body. If the health of ourselves is interrupted, it is also interrupted by someone to do the activity. There are several diseases that have a lot of sufferers. One of them is the disease of the respiratory system. Respiratory system is defined generally as a matter that disrupts the process of breathing in our body. Diseases of the respiratory system is one of the main problems of public health in Indonesia, because the disease is a human breathing. The expert system is a library of specialists or an expert in diseases of the respiratory system and the conditions used to take the conclusion of the symptoms. In the calculation process used the certanity factor method to find a percentage level of confidence. The Parameter used in the diagnosis is the symptom chosen by the sufferer. The conclusion of this application results in the diagnosis of the disease suffered and the percentage result of confidence through the selected symptoms. Keywords: Respiratory disease, expert system, Certainty Factor